Trends and patterns in Marriage and time spent single and sexually active in Sub Saharan Africa, a comparative analysis of six community based cohort studies. - (:unkn) unknown (My University, 2009)
Objectives To describe trends in age at first sex (AFS), first marriage (AFM) and time spent single between events. To compare age-specific trends in marital status in six cohort studies. Methods Cohort data from Uganda, Tanzania, South Africa, Zimbabwe and Malawi and DHS data from Uganda, Tanzania and Zimbabwe were analysed. Life table methods were used to calculate median AFS, AFM and time spent single. In each study, two surveys were chosen to compare marital status by age and identify changes over time. Results Median AFM is much higher in South Africa than in the other sites. Between the other populations there are considerable differences in median AFS and AFM (AFS from 17-19 for men and 16-19 for women, AFM from 21-24 and 18-19 respectively, for the 1970-79 birth cohort). In all surveys, men reported a longer time spent single than women (a median of 4-7 years for men, and 0-2 years for women). Median years spent single for women has increased, apart from in Manicaland. For men in Rakai it has decreased slightly over time, but increased in Kisesa and Masaka. The DHS data show similar trends to those in the cohort data. The age-specific proportions who are married have changed little over time. Conclusions Median AFS, age AFM and time spent single vary considerably among these populations. These three measures are underlying determinants of sexual risk and HIV infection, and they may partially explain the variation in HIV prevalence levels between these populations.
Keywords: African Research